2021
DOI: 10.1021/acs.langmuir.1c01576
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Sorption

Abstract: Understanding how sorption depends on temperature on a molecular basis has been made difficult by the coexistence of isotherm models, each assuming a different sorption mechanism and the routine application of planar, multilayer sorption models (such as Brunauer–Emmett–Teller (BET) and Guggenheim–Anderson–de Boer (GAB)) beyond their premises. Furthermore, a common observation that adsorption isotherms measured at different temperatures fall onto a single “characteristic curve” when plotted against the adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 72 publications
(221 reference statements)
0
29
0
Order By: Relevance
“…Results also showed that mean binding of the capture peptides at 4 h at room temperature was not significantly different compared to 16 h binding. However, mean binding for 4 h at 4 °C was significantly different to 16 h. This difference most likely dependent on variations in absorption kinetics at different temperatures for CH2 domain 32 . Overall, the results support the idea that the capture peptides can be easily attached to textiles, such as during routine laundry cycles 33 , 34 .…”
Section: Resultsmentioning
confidence: 83%
“…Results also showed that mean binding of the capture peptides at 4 h at room temperature was not significantly different compared to 16 h binding. However, mean binding for 4 h at 4 °C was significantly different to 16 h. This difference most likely dependent on variations in absorption kinetics at different temperatures for CH2 domain 32 . Overall, the results support the idea that the capture peptides can be easily attached to textiles, such as during routine laundry cycles 33 , 34 .…”
Section: Resultsmentioning
confidence: 83%
“…(This is reminiscent of the previous attempts to relate the Kirkwood–Buff approach to the hydration shell/bulk partition coefficient defined under hydration shell model and accessible surface area In this context, K I (0) is exponentially related to the free energy of sorption; whether this free energy is dominated by the energy or entropy can be revealed by the temperature dependence of an isotherm …”
Section: Resultsmentioning
confidence: 98%
“…Then, the second layer of N 2 molecules starts to gradually form, through the interaction with the already adsorbed molecules of the first layer. The condensation process is cooperative, [ 43,44 ] as shown by the third and further layers easily forming on the second one before it is saturated, which is reflected by the marked inflection of the adsorption isotherm.…”
Section: Resultsmentioning
confidence: 99%